Hidden in a group? Market reactions to multi‐violator corporate social irresponsibility disclosures - Liu, Chang; Wang, Stephanie Lu; Li, Dan (Strategic Management Journal, 2022)
Abstract Research Summary The media often discloses multiple firms' corporate social irresponsibility (CSI) behaviors together (i.e., multi‐violator CSI disclosures). Drawing on attribution theory, we propose that multi‐violator CSI disclosures artificially create “violator groups.” Such violator groups weaken the extent to which investors attribute each violator firm's CSI behaviors to the firm itself and subsequently lessen negative market reactions toward the violator firm. Further, the temporal consistency and context diversity of the focal firm's past CSI behaviors mitigate the relationship between CSI disclosure type (i.e., multi‐violator vs. single‐violator CSI disclosures) and stock market reactions. Empirical findings based on a sample of 1,369 CSI disclosures linked to 506 S&P 1500 firms between 2010 and 2017 support our hypotheses. Managerial Summary Some public media reports disclose multiple firms' CSI behaviors together, while others disclose only one firm's CSI behaviors at a time. These two different frames can result in very different stock market reactions. We find that while the stock market reacts negatively to media reports of firms' CSI behaviors on average, negative reactions are weaker when the media discloses multiple firms' CSI behaviors than when only one firm's CSI behaviors are disclosed. However, this difference in market reactions to multi‐violator versus single‐violator CSI disclosures is smaller for firms that have engaged in many CSI behaviors or have engaged in many different types of CSI behaviors before.